THE EFFECTIVENESS OF THE USE OF LEARNING VIDEOS ON THE UNDERSTANDING OF MATHEMATICS CONCEPTS IN ELEMENTARY SCHOOLS - Abul Walid; Ethan Tan; Ryan Teo (International Journal of Educatio Elementaria and Psychologia, 2025)
The abstract nature of many mathematical concepts presents a significant pedagogical challenge in elementary education, often leading to difficulties in student comprehension. The integration of multimedia, such as learning videos, offers a promising avenue to make these concepts more concrete and accessible. This study aimed to quantitatively determine the effectiveness of using learning videos on elementary school students’ understanding of mathematics concepts. A quasi-experimental, pre-test/post-test non-equivalent control group design was employed. The sample consisted of two fifth-grade classes, with one class (N=32) assigned as the experimental group utilizing learning videos and the other (N=32) as the control group receiving conventional, textbook-based instruction. Students’ conceptual understanding was measured using a validated, standardized mathematics concept test. Data were analyzed using an independent samples t-test and normalized gain scores. The results revealed a statistically significant difference in the post-test scores between the two groups (p < 0.01), with the experimental group demonstrating a substantially higher mean score and a significantly greater normalized gain. The study concludes that the use of learning videos is a highly effective instructional strategy for improving students’ understanding of mathematical concepts in elementary school.